2018
DOI: 10.1109/tbme.2017.2749371
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Wideband Millimeter-Wave Dielectric Characteristics of Freshly Excised Normal and Malignant Human Skin Tissues

Abstract: Millimeter waves have recently gained attention for the evaluation of skin lesions and the detection of skin tumors. Such evaluations heavily rely on the dielectric contrasts existing between normal and malignant skin tissues at millimeter-wave frequencies. However, current studies on the dielectric properties of normal and diseased skin tissues at these frequencies are limited and inconsistent. In this study, a comprehensive dielectric spectroscopy study is conducted for the first time to characterize the ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…where B is the system bandwidth and c is the speed of light in the target medium. Based on (1), it is suggested that to achieve an axial resolution of 200 μm in human skin tissue (with effective dielectric permittivity of 20 [18] ), an ultrawide imaging bandwidth of ~100 GHz is required [14].…”
Section: B Bandwidth and Aperture Size Requirements For High-resolution Imaging Systemsmentioning
confidence: 99%
“…where B is the system bandwidth and c is the speed of light in the target medium. Based on (1), it is suggested that to achieve an axial resolution of 200 μm in human skin tissue (with effective dielectric permittivity of 20 [18] ), an ultrawide imaging bandwidth of ~100 GHz is required [14].…”
Section: B Bandwidth and Aperture Size Requirements For High-resolution Imaging Systemsmentioning
confidence: 99%
“…Present investigations carried out through 60 on healthy and unhealthy skin tissues were gathered from skin cancer patients to measure dielectric properties at restricted frequency range of 0.5 to 50 GHz by comprehensive dielectric spectroscopy which is used for the first time to characterize the ultra‐wideband dielectric properties of freshly‐excised normal and malignant skin tissues. To estimate the effects of malignancy on the dielectric properties of the samples a multivariate analysis of variance (MANOVA) is applied.…”
Section: Dielectric Properties Of Skin Cancermentioning
confidence: 99%
“…It can quickly detect the dielectric properties of tissues, and there are no excessive requirements on the size, shape or physical form of the sample. [28][29][30][31] It has the advantages of being simple, fast, easy to operate, and noninvasive. Therefore, we chose frequencies of 1~4000 MHz to explore the dielectric properties of thyroid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We used the open‐ended coaxial line method, which is a common method for measuring the dielectric properties of human tissues. It can quickly detect the dielectric properties of tissues, and there are no excessive requirements on the size, shape or physical form of the sample 28–31 . It has the advantages of being simple, fast, easy to operate, and noninvasive.…”
Section: Introductionmentioning
confidence: 99%